When European meets African honeybees (Apis mellifera L.) in the tropics: Morphological changes related to genetics in Mauritius Island (South-West Indian Ocean) - (:unkn) unknown (My University, 2020)
The previous genetic characterization of the honeybee population of Mauritius Island (Indian Ocean) revealed an ongoing process of hybridization between the first established African subspecies Apis mellifera unicolor and recently imported European subspecies (A. m. ligustica, A. m. carnica and A. m. mellifera). This context offers the rare opportunity to explore the influence of hybridization between African and European honeybees on phenotypic traits out of the case largely studied of the Africanized honeybee (hybrid between A. m. scutellata from South Africa and European subspecies). We thus conducted geometric morphometric analyses on forewings of 283 workers genetically characterized at 14 microsatellite loci to evaluate (1) if the morphological variability coincides well with the neutral genetic variability, (2) if hybrids exhibited rather parental, intermediate or transgressive traits, and (3) to test if fluctuating asymmetry (FA) of size and shape, as a measure of developmental stability, was elevated in hybrids (due to genetic stress) and/or European bees (due to unsuitable environment) compared to African bees. A strong concordance was found between morphological variability and neutral genetic variability, especially for wing shape, based on partial least-square analyses (PLS). However, on average, the morphology of hybrids was more similar to the African bees, potentially reflecting the dynamics and direction of introgression. Significant FA for wing size as well as wing shape was detected, suggesting the overall presence of stress during the development of the studied individuals. In contrast, the asymmetry levels do not differ according to the ancestry (African, European or hybrid) of the individuals. Therefore, if ongoing hybridization contributed to increasing the genetic and phenotypic diversity of the populations and influences its adaptive potential, developmental stressors could not be identified and their evolutionary consequences
Keywords: African Research